Effects of a formulation of the veterinary drug moxidectin on the performance of a plant-insect food chain - Garcia, Andrés (2026)
The increasing use of veterinary anthelmintics, which mainly enter the environment via livestock feces, raises concerns about side effects on non-target organisms in agricultural landscapes. While most studies have focused on species at a single trophic level that are directly exposed to these drugs, little is known about their indirect effects on interacting species across trophic levels and the associated ecological functions. To address this research gap, we conducted the first experimental study on a terrestrial species assemblage exposed to soil spiked with a formulation of the commonly used veterinary anthelmintic moxidectin (MOXf). Using two mesocosm experiments, we tested a food chain composed of cultivated strawberry (Fragaria × ananassa, host), green peach aphid (Myzus persicae, herbivore), and marmalade hoverfly (Episyrphus balteatus, predator as a larva and pollinator as an adult). MOXf significantly reduced the number and weight of strawberry fruits by 24% and 32%, respectively. Aphid abundance increased by an order of magnitude on plants treated with MOXf, but only when no hoverfly larvae were present. In the presence of the predator, aphid abundance was reduced regardless of the treatment applied to the plant. Adult hoverflies exposed to MOXf-treated plants laid about four times as many eggs as the control group. We suspect that the anthelmintic drug weakens the plants' defense mechanisms against herbivores such as aphids, thereby fostering their reproduction. These results indicate that the role of veterinary drugs in shaping plant-insect interactions should be addressed more explicitly in ecotoxicological studies and environmental risk assessments.